To Increase Mental Health Literacy and Human Rights Among New-Coming, Low-Educated Mothers With Experience of War: A Culturally, Tailor-Made Group Health Promotion Intervention With Participatory Methodology Addressing Indirectly the Children - Ekblad, Solvig (Frontiers in Psychiatry, 2020)
Due to the increasing numbers of newcomers with impacts of war, civil war and persecution, at high risk of trauma-related mental health problems, there is a need for increase the poor mental health literacy (MHL) and human rights among the new-comers, especially low-educated mothers with children. This article aimed to present a case study report of several years’ experience of tailor-made group health promotion intervention. It describes as an example, a project during autumn 2018 in five municipalities of Sweden and in collaboration between academia, primary care, social welfare, police, and an NGO. Fifty-one women, Arabic- or Somalian speaking, with 1–7 children, mean age 40 years, low-educated and in average four years’ of living in Sweden participated. Under supervision, a local female member of the NGO coordinated the group meetings in Swedish with up to ten participants and the moderators were representatives of healthcare, social services and police/lawyer, with an interpreter present. Each intervention focused on human rights, health including mental health, psychosocial and parenting support, by using a 5-week group intervention a 2 h/week, totally 10 h excluding pre- and post-evaluation, and one language per intervention. Each meeting included 1-h lecture and after a short break with refreshments, the participants asked questions to the respective moderator. It was a mixed method but emphasis on qualitative design and participatory methodology with co-creation and evaluation of the intervention. The results showed that this tailor-made group intervention gave the participants empowerment and a sense of coherence, MHL and tools to deal with stress/anxiety, based on their needs that were mapped before in a pilot study during Spring 2018, indirectly addressing their children. However, they did not primarily talk about mental illness experience. It is vital that these interventions toward the target group with limited exposure to Western concepts (e.g., illness, anxiety, and trauma), may bridge the gap between Western and traditional cultural understanding of pre- and postmigration stress. In conclusion, MHL may be a function of both the cultural origin of the target group’s background and their resettlement in a Western reception country. Implications are discussed.